Economic Burden of Out-Of-Pocket Expenditure on Chronic Non-Communicable Disease Care in Southern Assam - Sarma, Munmi; Paul, Shanku; Roy, Dipanjan; Roy, Dipankar; Das, Jayashree; Dey, Biraj; Paul, Sandip R; Das, Pinak P (National Journal of Community Medicine, 2025)
Background: Hypertension and diabetes are major non-communicable diseases in India, and their treatment often requires lifelong care. In semi-urban Assam, where health facilities are limited and insurance coverage is weak, families depend heavily on out-of-pocket payments, which can quickly become a financial strain. Objectives: To estimate the treatment costs for these conditions in Silchar and examine the socio-demographic and behavioural factors linked with higher expenditure. Materials and Methods: A cross-sectional survey of 323 adults aged 30 years and above, all diagnosed with hypertension and/or diabetes, was carried out in Silchar between January and June 2025. Data on household profile, health behaviour, and costs were collected through a pre-tested questionnaire. Out-of-pocket costs included medicines, consultation, tests, travel, and wage loss. Statistical analysis used descriptive measures, non-parametric tests, and median regression. Results: The median cost per visit was ₹1,200-1,300 (approximately $14-16, using the average 2025 exchange rate of $1 ≈ 83 INR), with medicines forming about 72% of the total cost, representing the largest share. Higher costs were reported among older adults, self-employed, homemakers, unemployed, dependent individuals, and tobacco users. Insurance reduced costs slightly but without significant impact. Conclusion: Chronic disease care in Southern Assam continues to impose a heavy financial burden on households. Affordable medicines, inclusion of outpatient services under insurance, and preventive efforts such as tobacco control are essential, as dual tobacco use was associated with nearly 12% higher treatment costs.